2022
DOI: 10.1007/s00392-022-02075-2
|View full text |Cite
|
Sign up to set email alerts
|

Third dose of the BNT162b2 vaccine in cardiothoracic transplant recipients: predictive factors for humoral response

Abstract: Background We report the results of a prospective study on the immunogenicity of a 3rd dose of BNT162b2 in thoracic organ recipients with no or minimal response following a two-dose BNT162b2 vaccination scheme. Methods A total of 243 transplant recipients received a homologue 3rd dose. Anti-SARS-CoV2-immunoglobulins (IgGs) were monitored immediately before (T1), 4 weeks (T2) as well as 2 and 4 months after the 3rd dose. Neutralizing antibody capacity (NAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“… 98 Similar factors have been identified in other studies as associated with vaccine response 70,72,73,99 and also identified receipt within 12 months of ATG or rituximab as associated with impaired response 70 . In studies focusing on heart and lung transplant recipients, age and antimetabolite use were again found to be associated, including an identification of moderate and high dose MMFs (>1000 mg daily), but not low (<1000 mg daily) dose MMF, as associated with impaired response 77,100,101 . A meta‐analysis of factors important for SARS‐CoV‐2 vaccine response identified a negative impact of antimetabolite (OR 4.3 [95% CI 3.4–5.4]) and belatacept (OR 5.4 [95% CI 3.4–8.7]) use 102 .…”
Section: Review Of Response To Selected Vaccines Prior To Covid‐19supporting
confidence: 61%
“… 98 Similar factors have been identified in other studies as associated with vaccine response 70,72,73,99 and also identified receipt within 12 months of ATG or rituximab as associated with impaired response 70 . In studies focusing on heart and lung transplant recipients, age and antimetabolite use were again found to be associated, including an identification of moderate and high dose MMFs (>1000 mg daily), but not low (<1000 mg daily) dose MMF, as associated with impaired response 77,100,101 . A meta‐analysis of factors important for SARS‐CoV‐2 vaccine response identified a negative impact of antimetabolite (OR 4.3 [95% CI 3.4–5.4]) and belatacept (OR 5.4 [95% CI 3.4–8.7]) use 102 .…”
Section: Review Of Response To Selected Vaccines Prior To Covid‐19supporting
confidence: 61%
“…Furthermore, a fourth vaccine dose resulted in seroconversion in a few more cases. Numerous studies confirmed that a third dose of vaccine increased antibody response against SARS‐CoV‐2 in solid organ transplant recipients 11–13,25–29 . In light of these findings, it became evident that booster vaccine doses would be essential in the prevention strategy against SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 95%
“…In light of these findings, it became evident that booster vaccine doses would be essential in the prevention strategy against SARS‐CoV‐2. However, several recipients had insufficient immune response against SARS‐CoV‐2 indicating that alternative strategies may be needed to improve protection in some immunocompromised patients 26–28 . For those solid organ transplant recipients who do not have sufficient antibody titers after three vaccines, the ESOT suggests the administration of additional booster vaccine doses or the consideration of pre‐exposure prophylaxis with monoclonal antibodies 14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations